Case report: Corticosteroids-induced acute diabetic peripheral neuropathy - Yuan, Jia-Lin; Sun, Le; Su, Bao-Lin; Hong, Chuang-Xiong (Frontiers in Endocrinology, 2022)
A 62-year-old man was diagnosed as IgA nephropathy. He had a pancreatic tumor operation years ago and had a normal plasma glucose tested every year. 1month after the medication of prednisolone acetate was administered his fasting plasma glucose elevated to 7.1mmol/L and he manifested symptoms of thirsty, frequent urination and weight loss. Approximately 3 months after the steroids, he started complained of numbness, weakness and muscle cramp in his lower extremity, blood tests showed elevated plasma glucose and electromyography (EMG) revealed impairment of the peripheral nerves in the lower extremity, diabetic peripheral neuropathy was diagnosed. Mecobalamin and Acupuncture were employed and steroids was discontinued, 8 months later he retrieved part of his strength and sensation. This case presents a specific adverse drug reaction of corticosteroids that causes diabetes mellitus and subsequently leads to peripheral neuropathy in an acute onset.